Prefoldins: the new chaperones (Advances in Experimental Medicine and Biology,, 2018)
This book reviews recent work on molecular chaperones of the prefoldin family from their discovery in Archaea to the basic clarification of their structure. Even though, there is still a lot to investigate in order to understand the roles and functions of prefoldins, some preliminary work suggests their contribution in assembly and activation of a variety of macromolecular complexes. Hence, the reader is introduced to recent structural findings via cryo-electron microscopy and to the importance of this particular group of proteins in health and disease. This book also discusses the particular structure of the URI prefoldin-like complex. In addition, recent developments in the generation of URI mouse models speculate on the functions and emerging roles of the URI prefoldin-like complex in various cellular processes. This novel protein complex represents a unique cellular machinery, which molecular basis of its activity still remains to be determined. This work is thus a guide to help researchers in the field to have a more comprehensive and critical view of the prefoldin world.